Faktor Sumber Daya Manusia dalam Pengendalian Mutu Konstruksi Jalan - Siswosoebrotho, Bambang Ismanto; Ing, Tan Lie (Jurnal Teknik Sipil, 2005)
The quality of road construction is highly dependent on the quality of human resources of organizers, managers and also road users considering that the quality of construction is a product of construction activity actors including project owners (owners), contractors as implementers and also consultants both as planners and supervisors; but not to forget the road users. In general, the human resources owned by the perpetrators of activities are actually sufficient and have adequate 'abilities' both in the field of engineering and road construction, this can be seen from the large number of human resources who have attended and graduated from various training and development ranging from courses, training, education, etc. in the field of road engineering. However, the facts show that the quality of the road construction industry is still far from satisfactory as seen from the many premature damages to road construction. A new problem, the ethical problem, is relatively more complicated than the capability problem. The word 'ethics' may be too harsh and harsh, so it would be better to call it a 'culture' of willpower because it concerns not only road operators, but also road users. In general, it appears that all the problems of road construction, utilization and management are inadequate, especially those related to human resources in terms of the ethics of the human resources concerned. For this reason, it is necessary to rethink what “breakthroughs” can be made by institutions responsible for the quality of human resources.